Teaching Communications, Cultures, Connections, Comparisons, and Communities with Multimedia: A University-Middle School Service-Learning Project (LETRAS, 2008)
Se describe el uso de tecnología en forma de presentaciones de multimedia para facilitar la enseñanza de las Normas para el Aprendizaje de una Lengua Extranjera del Concilio Americano para la Enseñanza de Lenguas extranjeras. Las normas abarcan las comunicaciones, las culturas, las conexiones, las comparaciones y las comunidades. El estudiantado universitario aprende a crear, con multimedia, presentaciones sobre un tema cultural en la lengua meta. El componente de aprendizaje por servicio comunitario se fundamenta en las presentaciones creadas para estudiantes de colegio, quienes tienen acceso a las presentaciones en un sitio web de la universidad.A description is provided of how the use of technology in the form of multimedia presentations enhances the teaching of the Five C Standards for Foreign Language Learning of the American Council on the Teaching of Foreign Languages: communications, cultures, connections, comparisons, and communities. University students learn to create multimedia presentations on a cultural topic in the target language. The service-learning component provides the multimedia presentations for middle-school students who access them from the university website.